Chemical Composition and Aromatherapy-Based Relaxation Potential of Selected Indonesian Herbal Essential Oils - Nurina Rizka Ramadhania (ALCHEMY Jurnal Penelitian Kimia, 2026)
Aromatherapy, an alternative treatment approach, is gaining popularity in Indonesia due to its ability to provide psychological and physiological relaxation. The use of Indonesian herbal plants, especially Syzygium polyanthum (bay leaf), Camellia sinensis (green tea), Cymbopogon citratus (lemongrass), Lavandula angustifolia (lavender), and Citrus limon (lemon) in aromatherapy has long been recognized for its distinctive, refreshing aroma and diverse secondary metabolites. This scientific literature review is presented to reveal the relationships between the presence and diversity of chemical composition of selected Indonesian herbal plants and various influencing factors, such as plant origin and the extraction method used. The aroma-defining properties of eugenol, geraniol, linalool, citral, and limonene in essential oils, when combined, can synergistically trigger bioactivities, including antioxidant, antibacterial, anti-inflammatory, and relaxing effects. Scientifically, the relaxing effects of aromatherapy are produced through stimulation of the olfactory system, which connects to the limbic system in the brain, including the amygdala and hypothalamus, which are responsible for improving mood and enhancing emotional regulation. Based on this review, the metabolite profile of essential oils plays a role in determining their potential bioactivity, especially in selected herbal plants as sources of natural relaxation therapy.